Unprecedented long‐term survival in a patient with malignant pleural mesothelioma treated with subsequent systemic chemo‐ and immunotherapeutic regimens - Luigi Cerbone; Sara Delfanti; Antonina M. De Angelis; Stefania Crivellari; Francesco Boccuzzi; Angela Cimorelli; Marinella Bertolotti; Luisella Righi; Pietro Bertino; Federica Grosso (Thoracic Cancer, 2023)
Abstract Pleural mesothelioma is a rare disease with a dismal prognosis and few therapeutic options. Until recently the median overall survival for a pleural mesothelioma patient was up to 2 years, with few exceptional cases of patients achieving a longer survival. Here, we report the clinical case of a patient whose survival spanned over 10 years. The patient underwent several systemic treatments, including three different chemotherapy lines (cisplatin‐pemetrexed, vinorelbine and platinum rechallenge) and two immunotherapy regimens using immune checkpoint inhibitors (anti CTLA‐4 tremelimumab and anti PD‐1 nivolumab). At the time this report was written, the patient was off‐treatment, asymptomatic and with a stable radiological disease. Our case demonstrates that a prolonged survival with a preserved quality of life may be reached in selected patients through the exploitation of the available treatments in an expertise setting.